The use of spaceborne lidar to map Antarctic krill distributions and biomass in the Southern Ocean - Zhong, Chunyi; Chen, Peng; Zhang, Zhenhua; Xie, Congshuang; Zhang, Siqi; Sun, Miao; Wu, DanChen (Frontiers in Marine Science, 2024)
The Antarctic krill is a pivotal species in the Southern Ocean ecosystem, primarily due to its extraordinary nutritional content and plentiful resources. Studying the distribution of these resources and their environmental impact factors is crucial for the successful development of Antarctic krill fisheries. Traditional methodologies such as acoustic measurements, however, often face limitations in their capacity to provide a comprehensive and uninterrupted assessment. Moreover, the six-month duration of polar nights in polar regions presents significant challenges for traditional satellite observations. In this context, LiDAR, an active remote sensing observation method, offers a promising alternative. Known for their high resolution, flexibility, and efficiency, LiDAR systems can obtain detailed information on diurnal ocean parameters in polar regions on a vast scale and in a systematic way. Our study utilizes the spaceborne LiDAR system, CALIPSO, to successfully attain continuous Antarctic krill CPUE over the past decade, using various models such as the generalized linear model (GLM), artificial neural network (ANN), and support vector machine (SVM). A comparative analysis of the prediction results reveals that while both ANN and SVM models outperform the GLM, the SVM’s prediction capabilities are somewhat unstable. Our findings reveal CALIPSO’s potential in overcoming challenges associated with traditional satellite observations during polar winters. In addition, we found no obvious pattern of interannual variation in krill CPUE, with high values predominantly occurring from February to May. This suggests that krill is mainly located around the South Shetland Islands during January-April, before moving offshore towards South Georgia in May-June. A substantial krill aggregation community is found in the South Atlantic waters, indicating high potential for krill fishing. The optimum mix layer depth range for high krill CPUE is 270-390 m, with a chlorophyll concentration of approximately 0.1 mg m-3. The optimum sea surface temperature range is between -1.4-5.5°C, and the sea ice coverage range is approximately 0-0.1×106 km2. The predicted Antarctic krill bioresource has risen from 2.4×108 tons in 2011 to 2.8×108 tons in 2020. This increase in krill biomass aligns with the biomass of krill assessed by CCAMLR.